Impacts of the June 2011 Puyehue-Cordón Caulle volcanic complex eruption on urban infrastructure, agriculture and public health - Wilson, T. (2013)
Impacts of the June 2011 Puyehue-Cordón Caulle volcanic complex eruption on urban infrastructure, agriculture and public health in Argentina were studied by an interdisciplinary team from New Zealand, the United Kingdom and Argentina. The team also studied the emergency management of the eruption crisis. Field work was carried out between 27 February and 16 March 2012. Efforts were focused on the population centres that received the greatest ashfalls (Villa La Angostura, Bariloche and Ing. Jacobacci), and on agricultural  regions  affected by ashfalls